An Investigation on the Effect of the Total Efficiency of Water and Air Used Together as a Working Fluid in the Photovoltaic Thermal Systems - ATMACA, MUSTAFA (MDPI, 2019)
The temperature of a PV (photovoltaic) panel increases when it produces electricity but its electrical efficiency decreases when the temperature increases. In addition, the electrical efficiency of the PV panel is very limited. To increase the PV efficiency, the rest of the solar irradiance must be used, together with the temperature being kept at an optimum value. With this purpose, an experimental study was conducted. Firstly, two specific photovoltaic-thermal (PV/T) systems were designed. The first was the PV/T system which used only a water heat exchanger. The other one was the PV/T system that used a water and air heat exchanger. In the latter PV/T system, air passed through both the top of the PV panel and the bottom of it while water passed through only the bottom of the panel in a separate heat exchanger. In this way, the water and air absorbed the thermal energy of the panel by means of separate heat exchangers, simultaneously. In addition to the two systems mentioned above, an uncooled photovoltaic module was also designed in order to compare the systems. As a result, three different modules were designed. This study was conducted in a natural ambient environment and on days which had different climatic conditions. The thermal, electrical and overall efficiencies of each PV/T module were determined. The results were compared with the uncooled module electrical efficiency. The results showed that when water and air were used together, it was more efficient than single usage in a PV/T system. The thermal gain of the working fluids was also found to be fairly high and so, the gained energy could be used for different purposes. For example, hot air could be used in drying systems and air condition systems. Hot water could be used in hot water supply systems.
Keywords: water; and air-based PV; T system; water based PV; T system; total efficiency; natural ambient conditions; solar energy; SOLAR COLLECTOR; PERFORMANCE; VALIDATION; SIMULATION